STEPS TO BUILD STATIC CODE ANALYSIS TOOL TO DETECT VULNERABILITIES IN PHP PROGRAMMING LANGUAGE - Utepbergenov Yunus Qutlimuratovich (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the steps required to create an analytical tool that performs static analysis to identify vulnerabilities in the code of programs written in the Php programming language, which is one of the most widely used programming languages.